The Impact of the Post-Brexit Migration System on the UK Labour Market - Jonathan Portes; John Springford (Institute of Labor Economics (IZA), 2023)
The end of free movement and the introduction of the post-Brexit migration system represents a major structural change to the UK labour market. We provide a descriptive assessment of the impact on a sectoral basis. We examine how overall labour force growth has differed between sectors, both overall and in terms of the extent to which this growth was driven by migrant workers, both from the EU and from outside the EU, prior to the pandemic. This allows us to construct counterfactuals, which we contrast with observed outturns, as well as with data on visas issued by sector under the new system. Our analysis suggests that, although migration overall is currently running at least at pre-pandemic levels, the post-Brexit migration system has produced, as designed, a clear break with pre-Brexit trends, reducing labour supply for some sectors. There remains a substantial "shortfall" in migration for work, even taking of the impact of the pandemic. However, these impacts differ very considerably between sectors. In lower-skilled sectors, work-related migration under free movement does not appear to have been replaced by additional visa issuance under the new system. Meanwhile, in higher skilled sectors, increased visa issuance has increased, and does appear to be consistent with levels of migration that are broadly in line with pre-pandemic, pre-Brexit trends.
Keywords: F22; J48; J61; J68; 330; migration; labour markets; Brexit